Problems with Determining the Location of Land Objects Which Result in Differences in the Coordinate Points of Land Objects Listed on Land Certificates in Kendal Regency - Wahaningrum, Inti Rizki (TABELLIUS: Journal of Law, 2024)
Land ownership should be registered in order to obtain a certificate of proof of rights which can provide certainty and legal protection for the owner. Problems with the location of land objects being different from the coordinates stated on the certificate are caused by procedural errors in data collection, natural events and limitations in the level of accuracy of tools for taking coordinates. The solution to the problem of discrepancies in the location of land objects with the coordinates stated on the Certificate is through an objection mechanism by interested parties, which will then be re-examined on the land object and clarification will then be made to make a report on the correction. When the Certificate has been issued, the old certificate will be withdrawn and canceled and a new certificate issued.